2003
DOI: 10.1002/macp.200350074
|View full text |Cite
|
Sign up to set email alerts
|

Homolysis and Decomposition of Alkoxyamines Containing PROXYL and TEMPO Residues: A Comparison

Abstract: Quantitative ESR and 1H NMR spectroscopies have been used to study the homolysis and decomposition, respectively, of alkoxyamines derived from TEMPO and PROXYL nitroxides. It is shown that alkoxyamines substituted in the β position with a tert‐butoxy group have different activation parameters than those bearing a 1‐phenethyl fragment, however, there is compensation between transition state enthalpy and entropy, resulting in most cases in similar transition state free energies and homolysis kinetics. On the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…It can be assumed that the type of substituent in the isobutyrate‐2‐yl alkyl structure has no effect on the H‐atom transfer reaction. With TEMPOc 19 ( f D = 3.5%) and TEMPOb 17 ( f D = 2.2%), it was shown that the substituent on the ester group has no significant influence on the occurrence of the intermolecular H‐atom transfer reaction. Analyzing the experimental data for 10b and 10c , one can argue that 10b should also undergo the intermolecular H‐atom transfer reaction.…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that the type of substituent in the isobutyrate‐2‐yl alkyl structure has no effect on the H‐atom transfer reaction. With TEMPOc 19 ( f D = 3.5%) and TEMPOb 17 ( f D = 2.2%), it was shown that the substituent on the ester group has no significant influence on the occurrence of the intermolecular H‐atom transfer reaction. Analyzing the experimental data for 10b and 10c , one can argue that 10b should also undergo the intermolecular H‐atom transfer reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the efficiency of this kind of nitroxide to control the polymerization of styrene has been previously established 14–17. The analysis of the H‐transfer reaction occurring for alkoxyamines presented in Chart leads to investigate the polymerization of methyl methacrylate with nitroxide 10 , which demonstrated the absence of hydrogen abstraction during its decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the energy of activation of homolysis is a good estimate of the bond dissociaton energy (BDE) for the C‐ON bond 60, 61. We determined BDE from quantum mechanical calculations and compared it with the E a values obtained by experimental study (Table 2).…”
Section: Resultsmentioning
confidence: 99%